Leaching and availability of potassium in soil affected by conventional and coated fertilizer sources1 - Ribeiro, Bruno N. [UNESP]; Coelho, Anderson P. [UNESP]; Souza, Juscelio R. de; Gissi, Luciano de; Lemos, Leandro B. [UNESP] (FapUNIFESP (SciELO), 2022)
The use of coated fertilizers is a strategy for improving fertilization efficiency and crop yield. However, further studies are needed to understand the dynamics of different types of coated K fertilizers in the soil. The objective of this study was to evaluate K dynamics in soil columns after the application of conventional KCl and other K sources with coating (KCl-C) and compaction (KCl-CC) combined with the use of additives and polymers. The experiment comprised four treatments, consisting of three sources of K [conventional KCl, KCl coated with additives and polymers (KCl-C), and KCl compacted and coated with additives and polymers (KCl-CC)], and a control without K application, with four repetitions. The K concentration was evaluated in the leached solution collected from the soil columns for 28 days. After this period, the K concentration in the soil was determined. The absence of K fertilization in the soil led to a 26.5% reduction in the K concentration. The coated sources had lower granule hardness and higher K leaching than conventional KCl. The amounts of K leached were 62.2%, 68.5%, and 54.0% for KCl-CC, KCl-C, and conventional KCl, respectively. However, at the end of the experiment, the soil K concentration was higher under the KCl-C treatment.
Lixiviação e disponibilidade de potássio no solo afetadas por fontes de fertilizantes convencionais e revestidos
Keywords: polymers; potassium chloride; potassium fertilization; potassium fertilizers